Estrutura foliar de Byrsonima coccolobifolia Kunth. (Malpighiaceae) e PalicourearigidaKunth. (Rubiaceae) em ambiente de cerrado e campo rupestre - Gavilanes, Manuel Losada (2016)
The objective of this research was to conduct a qualitative and quantitative study on the anatomical characteristics of Byrsonima coccolobifolia Kunth. (Malpighiaceae) and Palicourea rigida Kunth. (Rubiaceae) leaves, species that occur in the Cerrado and Campo Rupestre montane savanna. The anatomical observations were made in fresh or fixedleaves, treated according to standard methodologies in plant anatomy. The following characteristics were observed in Byrsonima coccolobifolia: epidermis of the petiole and leaf blade unstratified; paracitic stomata present on the abaxial surface of the leaf blade; mesophyll with palisade parenchyma consisting of a single cell layer; spongy parenchyma with five to seven cell layers, with irregular shapes and varying sizes; crystal idioblasts containing druses or monocrystals of calcium oxalate, observed in all the parenchyma of the petiole and leaf blade; vascular collateral bundles; subepidermal collenchyma in the petiole and larger ribs, on both sides; the general veining pattern of the species is pinned, camptodromous, brochidodromous. The following characteristics were observed in Palicourea rigida: epidermis of the petiole and leaf blade unstratified; presence of trichomes, simple, uniseriate, near or on the ribs; paracitic stomata present on the abaxial surface of the leaf blade; mesophyll with palisade parenchyma consisting of a single cell layer; spongy parenchyma with seven to nine cell layers, with irregular shapes and varying sizes; crystal idioblasts containing druses, raphides and calcium oxalate styloids, observed in all the parenchyma of the petiole and leaf blade; vascular collateral bundles; subepidermal collenchyma in the petiole and larger ribs on both sides; the general veining pattern of the species is pinned, camptodromous, brochidodromous. Micromorphometric analyses for both species showed significant differences in all analyzed items (epidermis, mesophyll, stomata, leafdimensions, among others), and the highest averages were found in the leaves of plants growing in the Cerrado. This suggests that the influence of environmental factors may have modulated quantitative responses in plants, since no morphological changes were observed in the type and distribution of tissues in leaves, for both environments.